Validity of Pulse Express PRO in measurement of heart rate variability - Pagaduan, J. C.; Chen, Y. S. (German Journal of Exercise and Sport Research, 2021)
This study aimed to examine the validity of Pulse Express PRO, a free mobile application for measurement of heart rate variability (HRV). Thirty healthy male volunteers underwent simultaneous 5-min seated HRV recording from lead II electrocardiogram (ECG) and Pulse Express PRO (PE PRO). The raw R-R data after 5-min recording (PE PROraw) and HRV values displayed on smartphone PE PRO screen (PE PROdisplay) were examined using the ECG data as criterion. HRV measures that were evaluated included the standard deviation of normal-to-normal intervals (SDNN), root mean square of the successive differences in R-R intervals (RMSSD), normalized low frequency of power spectrum (LFnu), normalized high frequency of power spectrum (HFnu), and LF/HF ratio. Concurrent criterion validity was established from the typical error of estimate (TEE) of linear regression and Pearson`s correlation coefficient (r). Results revealed that HRV values (SDNN: TEE = 0.24, r = 1.00; RMSSD: TEE = 0.92, r = 1.00; LFnu: TEE = 0.75, r = 1.00, HFnu: TEE = 0.75, r = 1.00; LF/HF: TEE = 0.08, r = 1.00) in PE PROraw posted acceptable validity. On the other hand, only RMSSD (TEE = 1.05, r = 1.00) in PE PROdisplay was a valid HRV index. Thus, PE PRO can serve as an alternative tool for assessment of autonomic modulation.